ХОЙД МОНГОЛЫН ДЕВОНЫ ШҮЛТЛЭГ ГРАНИТОИД ЧУЛУУЛГИЙН ПЕТРОГРАФИ БА ХИМИЙН НАЙРЛАГА - Л.Жаргал; Л.Оюунжаргал (Geological Issues, 2023)
ХОЙД МОНГОЛЫН ДЕВОНЫ ШҮЛТЛЭГ ГРАНИТОИД ЧУЛУУЛГИЙН ПЕТРОГРАФИ БА ХИМИЙН НАЙРЛАГА